2022
DOI: 10.1111/fwb.13905
|View full text |Cite
|
Sign up to set email alerts
|

The gut bacterial microbiome of the Threeridge mussel, Amblema plicata, varies between rivers but shows a consistent core community

Abstract: 1. Freshwater mussels are important for nutrient cycling and ecosystem health as they filter feed on their surrounding water. This filter feeding makes these bivalves especially sensitive to conditions in their environment. Gut microbial communities (microbiomes) have been recognised as important to both host organism and ecosystem health; however, how freshwater mussel microbiomes are organised and influenced is unclear.2. In this study, the gut bacterial microbiome of Threeridge mussel, Amblema plicata, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…An increasing number of studies have characterized the gut microbiome of freshwater mussels [3,[42][43][44][45][46][47][48][49]. Many of these studies report similar findings to the current study in that the most abundant bacterial phyla in the guts of freshwater mussels are Firmicutes, Proteobacteria, and Planctomycetes [3,45,47].…”
Section: Discussionsupporting
confidence: 81%
“…An increasing number of studies have characterized the gut microbiome of freshwater mussels [3,[42][43][44][45][46][47][48][49]. Many of these studies report similar findings to the current study in that the most abundant bacterial phyla in the guts of freshwater mussels are Firmicutes, Proteobacteria, and Planctomycetes [3,45,47].…”
Section: Discussionsupporting
confidence: 81%
“…Stevick et al (2021) observed that the gut microbiomes of non‐depurated C. virginica vary spatially over their range in Narragansett Bay with important covarying environmental factors such as temperature, salinity, dissolved oxygen and nutrients. Similar effects of the site have been observed in the gut microbiomes of non‐depurated freshwater bivalves (Chiarello et al, 2022; Lawson et al, 2022). The gut microbiomes of non‐depurated bivalves have also been demonstrated to vary temporally over both years (McCauley et al, 2021) and seasons (Akter et al, 2023; Conceição et al, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…A ‘core’ microbiome, as it is most commonly defined (i.e., taxa present in most or all samples), is not synonymous with a resident microbiome. In the bivalve‐associated microbiome literature, researchers have identified ‘core’ microbial communities and either directly implied that the ‘core’ taxa were residents or indirectly implied it by using ‘core’ as the opposite of transient (King et al, 2012; Lawson et al, 2022; Zheng et al, 2021). Even if a taxon is recovered in all samples across spatial or temporal spectra, if the host had not voided transient material at the time of sampling, then the ‘core’ taxa could be transient.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have relied upon the presence of bacterial fatty acids such as C18:1 to assess the consumption of bacteria but these fatty acids are also abundant in algal chloroplasts 58 raising the possibility that algal fatty acids could have been mistaken as bacterial. Freshwater mussels also sustain an endosymbiotic gut microbiome 59 which is established from bacteria filtered from the environment that are not digested 60 , 61 . Therefore it is possible that some earlier studies mistook the microbiome for consumed bacteria 23 .…”
Section: Discussionmentioning
confidence: 99%